CHALLENGING FAMILIAR ASSUMPTIONS Preparing for and initiating a self-directed group - Mullender, Audrey; Ward, David (Groupwork, 1989)
The self-directed groupwork approach aims to empower group members to set their own goals for external change. The membership of self-directed groups is often, voluntary and non-selected. In this paper, the preliminary stages of the approach are examined in detail and are contrasted with more conventional groupwork methods. A key feature of self-directed groupwork is that workers must begin by thrashing out an agreed and explicit value position from which their practice will flow. They then embark upon a process of ‘open planning’ in which, rather than making all the initial decisions for the group, they hand over as much responsibility as possible to the members. Neither the length of the group nor the frequency of meetings is pre-determined; members themselves decide on the timing and location of meetings. The conduct of the group is also negotiated by workers and members together. The message to be conveyed is that the group belongs to its members right from the start. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are to some extentsearchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.